(untitled) (Environmental Smoke, 2024)
The Vertebral arteries correspond to a pair of vessels that originate from the superior branch of the 1st portion of the A. Subclavia. In general, they present general anatomical variations regarding the length and diameter of the lumen, with the left being larger than the right. More extreme variations, such as the absence of one of the arteries, due to agenesis or involution, are generally related to craniovertebral defects. The objective of this work was to evaluate the anatomical variations found in the vertebral arteries and to discuss their clinical implications. In the construction of this study, a descriptive research, of the RIL type, was carried out, fulfilling all the stages of development. The search resulted in 23 articles. After reading, the corpus was composed of 12 articles, whose potential content was dedicated to investigating the type of anatomical variation of the vertebral artery and its implications and harms in the health of the carriers. Symmetrical vertebral arteries are found in about 26% of individuals. Marked differences in the diameter of the arteries, called Vertebral Artery Dominance (VAD) result in a significant decrease in the blood flow velocity of the artery and an increase in the resistance index (RI). The incidence of infarction in the posterior region of the brain is significantly higher in individuals with VAD. Infarctions occurred more frequently on the side of the non-dominant vertebral artery, probably due to non-mixing of Aa blood. vertebral arteries within the A. basilar, which run separately and with a central zone where flow is absent, called the "dead spot". Changes in normal blood flow were tested to determine their correlations with sites of thrombosis and atherosclerosis in humans. The agenesis of some branches of A. vertebral is also identified as an important factor for the occurrence of strokes in the posterior region of the brain.